PENGARUH SIKAP, NORMA SUBJEKTIF, DAN KONTROL KEPERILAKUAN YANG DIPERSEPSIKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA BATU - Teddy Briand Samudra; Maslichah Maslichah; Dwiyani Sudaryanti (Universitas Islam Malang, 2020)
The purpose of this study was to determine the relationship between attitudes, subjective norms, and perceived behavioral control towards compliance individual taxpayer. This study used design with a questionnaire as an instrument. Respondents in this study is the micro, small, and middle industry in Batu City. The Sample was selected using purposive sampling method and obtained with 106 respondent from the amount population 15.525. Data analysis techniques applied are classic assumption test, multiple linear regression, and multiple linear regression. The results of the research show that: (1) Attitude has positive and significant influence shown of 0,024 and value of significant < level of significant (0,024< 0,050); (2) Subjective Norm has positive and significant influence of 0,008 and value of significant < level of significant (0,008 < 0,050); (3) Perceived Behavioral Control has positive and significant influence of 0,000 and value of significant < level of significant (0,000 < 0,050); (4) Attitude, Subjective Norm, and Perceived Behavioral Control has positive and significant impact simultaneously shown and value of significant < level of significant (0,000 < 0,050). Keywords: Attitude, Subjective Norm, and Perceived Behavioral Control, Individual Taxpayer Compliance in Batu City.